The origin of the recent (2012-2016) seismic activity in the Guadalajara, Jalisco, Mexico, area: A block boundary interaction? - Jaime Yamamoto; Juan M Espíndola; A Zamora-Camacho; Guillermo Castellanos (PLoS ONE, 2018)
The central part of Jalisco, Mexico, has experienced low-magnitude earthquake sequences and swarms. Although the effects of these earthquakes have been limited to relatively small areas, the earthquakes have caused general alarm among the population and, in some cases, have been catastrophic. These earthquake swarms are significant because they affect the most populous area of the state, including the capital city of Guadalajara. An extraordinary example is an earthquake swarm that started on 8 May 1912 and lasted until September of that year. The region remained seismically quiescent until May 2012, when seismic activity resumed, lasting to the present. We analyze the recent seismic activity, starting with the earthquake of 18 May 2012 (03:07 UT) at the western edge of Lake Chapala and ending with the magnitude 4.2 earthquake on 3 November 2016. Our analysis includes eight earthquakes with magnitudes between 3.5 and 4.8, the revision of hypocenter locations, and the determination of focal mechanism solutions using the inversion of the moment tensor method. When possible, inversion solutions are compared with solutions obtained with the first arrival polarity method. We compare our results for the recent seismicity with the distribution of reported damage associated with historical earthquakes. Our work indicates a N-S trending seismic source zone and an orientation of nodal planes that suggests reactivation of preexisting local faults induced by the interaction of the western border of the Trans-Mexican Volcanic Belt with the eastern border of the Jalisco Block.